A short-term high-fat diet alters rat testicular activity and blood-testis barrier integrity through the SIRT1/NRF2/MAPKs signaling pathways - Falvo, Sara; Minucci, Sergio; Santillo, Alessandra; Senese, Rosalba; Chieffi Baccari, Gabriella; Venditti, Massimo (Frontiers in Endocrinology, 2023)
Background Overweight/obesity are metabolic disorder resulting from behavioral, environmental, and heritable causes. WHO estimates that 50% of adults and 30% of children and adolescents are overweight or obese, and, in parallel, an ongoing decline in sperm quality and male fertility has been described. Numerous studies demonstrated the intimate association between overweight/obesity and reproductive dysfunction due to a highly intricate network of causes not yet completely understood. This study expands the knowledge on the impact of a short-term high-fat diet (st-HFD) on rat testicular activity, specifically on steroidogenesis and spermatogenesis, focusing on the involved molecular mechanisms related to mitochondrial dynamics, blood-testis barrier (BTB) integrity, and SIRT1/NRF2/MAPKs pathways. Methods Ten adult Male Wistar rats were divided into two groups of five and treated with a standard diet or an HFD for five weeks. At the end of the treatment, rats were anesthetized and sacrificed by decapitation. Blood was collected for serum sex hormone assay; one testis was stored at -80ÅãC for western blot analysis, and the other, was fixed for histological and immunofluorescence analysis. Results Five weeks of HFD results in reduced steroidogenesis, increased apoptosis of spermatogenic cells, and altered spermatogenesis, as highlighted by reduced protein levels ofmeiotic and post-meiotic markers. Further, we evidenced the compromission of the BTB integrity, as revealed by the downregulation of structural proteins (N-Cadherin, ZO-1, occludin, connexin 43, and VANGL2) other than the phosphorylation of regulative kinases (Src and FAK). At the molecular level, the impairment of mitochondrial dynamics (fission, fusion, andbiogenesis), and the dysregulation of the SIRT1/NRF2/MAPKs signaling pathways, were evidenced. Interestingly, no change was observed in the levels of pro-inflammatory markers (TNFα, NF-kB, and IL-6). Conclusions The combined data led us to confirm that overweight is a less severe state than obesity. Furthermore, understanding the molecular mechanisms behind the association between metabolic disorders and male fertility could improve the possibility of identifying novel targets to prevent and treat fertility disorders related to overweight/obesity.